COLLABORATION LOCAL GOVERNMENT IN RURAL AREA DEVELOPMENT IN KAMPAR REGENCY RIAU PROVINCE - Rahman, Khairul (Department of Government, FISIP, Universitas Padjadjaran, 2022)
The regional government has the authority to accelerate the development of some rural areas through the development of the rural regions as a form of extra encouragement from the provincial government. Rural Area Development combines inter-village action in one Regency/City to accelerate and improve the quality of services, development, and empowerment of Village communities in Rural Areas through a participatory development approach. Three villages are proposed based on the inventory and identification carried out by the local government of the Kampar Regency. They will be implemented in developing rural areas, namely Pulau Gadang Village, Koto Mesjid Village, and Tanjung Alai Village, which have links to leading tourism commodities (Lake tourism rural areas). Based on the facts in the field, there are several problems related to rural areas' development, namely land status, regulation of tourist objects, and boundaries between villages. Therefore, collaboration is needed in developing rural areas, where the local government of Kampar Regency must involve the active role of the central government, provincial government, village governments, community leaders, and companies around tourist attraction areas and universities. This study uses a qualitative method with the primary objective of being descriptive and revealing (to describe and explore). The results of the study found that the collaboration of the local government of Kampar Regency in the development of rural areas has not run optimally; this is because there is no unity of action (harmony) between collaborating elements and common perception, commitment, and motivation.gb777